The common agricultural policy—Where now? - Nick Butler (Intereconomics, 1984)
The outcome of the Athens and Brussels summits was a cruel disappointment for all European optimists. The brunt of the consequences of this diplomatic failure will be borne by the Common Agricultural Policy. Is it now time to write its obituary?
Keywords: 330; EC